2015
DOI: 10.1002/ptr.5380
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Useful in Respiratory Disorders: Focus on Side-Effect Neutralizing Combinations

Abstract: This review summarizes literature related to medicinal plants reputed in traditional medical systems for treatment of asthma and coughs. The plants that are pharmacologically investigated for their effectiveness in such conditions, along with respective experimental protocol details, are also discussed. Some of plant origin compounds, which are considered useful as antitussive and antiasthmatic agents, are described as well. Chrysoeriol, a constituent of Aspalathus linearis (Fabaceae) was observed to be select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 100 publications
(74 reference statements)
0
7
0
2
Order By: Relevance
“…Besides, combined pharmacological activities of medicinal plants may exert adverse effect. [ 31 ] Consequently, the safety of YPFF needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, combined pharmacological activities of medicinal plants may exert adverse effect. [ 31 ] Consequently, the safety of YPFF needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported co-existence of PDEIs component(s) with Ca ++ antagonist(s) in some medicinal plants [6568]. As, combination of PDEIs and Ca ++ antagonists have synergistic spasmolytic interaction in smooth muscles (more effective in respiratory system) and opposing/side effects neutralizing effects in heart [69], hence might making the plant more efficacious to relax airways, compared to cardiac muscles.…”
Section: Discussionmentioning
confidence: 99%
“…However, attentions should be given to the adverse events of YPFF because of only three trials (Cai and Cai, ; Ma and Liu, ; Zhang, ) reported the safety as outcome. Importantly, combinations of pharmacological activities in medicinal plants might exert adverse effect‐neutralizing/synergistic potential (Khan and Gilani, ). Therefore, the safety of YPFF needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%